2006
DOI: 10.1051/forest:2005105
|View full text |Cite
|
Sign up to set email alerts
|

Beech (Fagus sylvaticaL.) – Technological properties, adhesion behaviour and colour stability with and without coatings of the red heartwood

Abstract: -European beech (Fagus sylvatica L.) is a popular and major tree species in Europe. The economic value of its timber is greatly decreased by the red heart phenomenon. The cause of red heart formation is well understood. However, scientific investigations about the technological and mechanical behaviour of red heartwood are scarce. Our study aims to provide a sound scientific basis for the characterization of technological properties, adhesion-as well as colour-behaviour of red-hearted beech. The mechanical and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 8 publications
0
24
1
1
Order By: Relevance
“…The economic importance of beech has increased in recent years because of the continuous demand for bright and evenly colored grades of logs and sawn timber (Pöhler et al, 2006). However, the occurrence of red heart amongst older trees and the consequences of mechanical wounding to the lower parts of stems, which occurs during forestry operations in unevenly managed forests, decrease wood quality and even increase timber loss.…”
Section: Introduction 1 Uvodmentioning
confidence: 99%
See 1 more Smart Citation
“…The economic importance of beech has increased in recent years because of the continuous demand for bright and evenly colored grades of logs and sawn timber (Pöhler et al, 2006). However, the occurrence of red heart amongst older trees and the consequences of mechanical wounding to the lower parts of stems, which occurs during forestry operations in unevenly managed forests, decrease wood quality and even increase timber loss.…”
Section: Introduction 1 Uvodmentioning
confidence: 99%
“…However, the occurrence of red heart amongst older trees and the consequences of mechanical wounding to the lower parts of stems, which occurs during forestry operations in unevenly managed forests, decrease wood quality and even increase timber loss. Discolored beech wood has a lower value on the market today than unaffected wood, due to its unfavorable technological properties, including hard impregnation, problems in drying processes and veneer production and, fi nally, its esthetic defi ciency (Koch et al, 2000;Pöhler et al, 2006).…”
Section: Introduction 1 Uvodmentioning
confidence: 99%
“…One of the main deficiencies of this tree species is its tendency to develop discolored wood in the central part of the tree, often called red heart, red heartwood, facultatively colored heartwood, false heartwood or red core (Bosshard, 1974;Torelli, 1984;Shigo, 1986;Sachsse, 1991;Wernsdörfer et al, 2005). As opposed to normal wood, discolored beech wood is characterized by its unfavorable technological properties, including hard impregnation, problems in drying processes and veneer production and esthetic insufficiency (Koch et al, 2000;Pöhler et al, 2006). In addition, wood of trees from unevenly managed forests is regularly subjected to mechanical wounding, which results in a relatively predictable response of the tree.…”
Section: Uvodmentioning
confidence: 99%
“…Studies on the short-term strength of defect-free, standardised specimens have revealed a variety of suitable adhesive types. These tests have shown that the short-term strength of test specimens, unaged prior to testing, was not affected sufficiently by adhesive type, amount of red heartwood (a species-inherent discoloration) or steaming level of the lamellae (Frühwald et al, 2003;Ohnesorge et al, 2006;Pöhler et al, 2006). Indeed, the longitudinal tensile shear strength tests carried out on structural adhesives before their approval and classification (EN 301:2006) must be conducted using beech timber.…”
Section: Introductionmentioning
confidence: 99%
“…al., 2006Ohnesorge et. al., , 2008Pöhler et al, 2006). The investigations conducted by Glos and Lederer (2000) and Blaß et al (2005), which form the basis of the impending gen-* Corresponding author: institut@fobawi.uni-freiburg.de eral building approval guidelines by the German Institute of Civil Engineering in Berlin (Z-9.1-679, Deutsches Institut für Bautechnik, 2009), in particular, have recommended beech glulam beams as a reliable, versatile construction product for use in moderate climates specified as service class I according to EN 1995EN -1-1:2004 One major challenge is to ensure that beech glulam bond integrity, especially bond durability, is adequate.…”
Section: Introductionmentioning
confidence: 99%